Penyelesaian Perkara Perdata Perbuatan Melawan Hukum Tanah Waris Berakhir Dading: (Studi Kasus No.22/PDT.G/2022/PN.TBN) - Achmad Wildan Dimyati; Vivin Astharyna Harysart; Ruminingsih Ruminingsih; Teguh endi widodo; Marwan Marwan; Arina jumiawati (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The application of social interaction in social life in society is not always harmonious. What happened is a difference in thoughts, opinions, and desires between one person and another. This difference became the origin of dispute or conflict in society. This ultimately encouraged those who started out modern-minded to develop dispute resolution mechanisms from their simplest form to what is now called the judicial system, which refers to positive law and social norms or rules. By using normative juridical research methods, namely research through a case approach, because this study aims to determine the efforts to resolve and legal consequences in the Tuban District Court Decision No. 22/Pdt.G/2022/PN.Tbn which is associated with applicable legal regulations and theories. In principle, the conciliation process can only proceed if the parties of the conflict act in good faith. The agreement reached is actually the result of mutual agreement, so that the deed of peace has the same legal force as a court decision (verdict) that is final and binding, and all legal remedies against permanently binding conciliation decisions/notices have ended.